Pemberdayaan Masyarakat Dalam Pencegahan Penyakit Diabetes Melitus Tipe II - sangadji, faisal (LPPM STIKES Madani, 2023)
WHO describes the incidence of Diabetes Mellitus (DM), which has increased quite rapidly, especially Type 2 DM. Type 2 DM is also at high risk of causing various complications due to a lack of knowledge, understanding, and ability of the community to prevent Type 2 DM. The same condition is also experienced by the community of Dusun Kradenan Nyamplung, which so far has not been exposed to education or training related to the prevention of Type 2 DM. The purpose of this service is to anticipate the increasing incidence of Type 2 DM through community empowerment in the prevention of Diabetes Mellitus. This service activity involved the health cadres of Dusun Kradenan Nyamplung and it was conducted from 23 May to 22 July 2022 with 20 participants and involved health cadres in Kradenan Nyamplung . the cadres were empowered and taught how to examine and provide health education regarding the prevention of Type 2 DM.. The result of the activity is an increase in the knowledge of cadres and the community about how to prevent diabetes mellitus. Cadres can also check blood glucose and provide health education. From the results of temporary blood glucose checks by cadres and accompanied by servants, it was found that 20% of people with GDS were more than 200 mg/dL.